2020
DOI: 10.3390/cancers12071995
|View full text |Cite
|
Sign up to set email alerts
|

Do Elderly Lung Cancer Patients Aged ≥75 Years Benefit from Immune Checkpoint Inhibitors?

Abstract: Lung cancer patients ≥75 years represent nearly 40% of all lung cancer patients and continue to increase. If elderly patients have a good performance status and adequate organ function, they can be treated the same as non-elderly patients. However, few comparative studies limited to elderly patients (≥75 years) have been conducted. We review the evidence on using immune check inhibitors for the treatment of elderly patients (≥75 years old) with advanced non-small cell lung cancer. Prospective randomized or non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Despite the difficulty of enrolling elderly patients in clinical trials, few real-world experiences of elderly patients with non-small cell lung cancer (NSCLC) and renal cell cancer (RCC) treated with ICIs have shown a similar efficacy, without a detrimental effect in tolerance compared to younger patients [8][9][10][11][12][13][14]. Moreover, in a recent metanalysis of six studies on NSCLC that compared ICIs with chemotherapy in the first or subsequent line of therapy, the hazard ratio (HR) for overall survival (OS) was comparable between patients < or ≥75 years (HR = 0.87; 95% CI: 0.56-1.35) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the difficulty of enrolling elderly patients in clinical trials, few real-world experiences of elderly patients with non-small cell lung cancer (NSCLC) and renal cell cancer (RCC) treated with ICIs have shown a similar efficacy, without a detrimental effect in tolerance compared to younger patients [8][9][10][11][12][13][14]. Moreover, in a recent metanalysis of six studies on NSCLC that compared ICIs with chemotherapy in the first or subsequent line of therapy, the hazard ratio (HR) for overall survival (OS) was comparable between patients < or ≥75 years (HR = 0.87; 95% CI: 0.56-1.35) [15].…”
Section: Introductionmentioning
confidence: 99%
“…The Impower150 [ 18 ] and Impower131 [ 19 ] studies compared ICIs plus chemotherapy with chemotherapy in four age groups (65, ≥65 to <75, ≥75 to <85, and ≥85 years). The HR of patients in this trials, who were 75–84 years old, was 0.78 (0.50–1.76) in the Impower 150 study and 0.74 (0.45–1.23) in the Impower 131 study, not indicating a significant OS benefit in patients ≥75 years old [ 20 ]. In our study, the median PFS and OS for the ICI + chemotherapy group were 5.3 and 10.7 months, respectively, which had no obvious advantage in improving survival in older patients compared with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the population with the most significant survival benefit in the ICIs era was patients under 75 years old, and age was negatively correlated with OS. Even Takigawa et al [ 9 ] pointed out that ICIs were not shown to be more effective than chemotherapy alone in NSCLC patients aged ≥ 75 years. Our findings partially support the notion that ICIs show reduced efficacy in elderly NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies focus on the administration of ICIs to elderly NSCLC patients. Taking nearly half of NSCLC patients who are 75 years and older in the real world into account [ 9 , 10 ], there is an urgent need for high-quality studies exploring the potential survival benefits of ICIs in those patients.…”
Section: Introductionmentioning
confidence: 99%